PsycEXTRA Dataset 2005
DOI: 10.1037/e530422013-001
|View full text |Cite
|
Sign up to set email alerts
|

Becoming and Being an Opera Singer: Health, Personality, and Skills

Abstract: The present thesis explores factors and processes associated with the artistic profession and development of opera singers. The profession of opera singers has a long story deriving its origin in early 1600s in Italy. What is performed on opera stages today is written in the musical scores in the 18 th and 19th century. The question arises how the modern opera singers live, learn and excel in their contemporary pursuit in order to meet the high demands on performance. The initial study identified health issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 201 publications
1
5
0
Order By: Relevance
“…However, the complete sample was relatively homogenous in musical competence, as the music students had passed entrance exams in high competition at prestigious music colleges. In accordance with the literature, vocal students started taking formal lessons later compared to instrumental students (Jørgensen, 2001, Sandgren, 2005). A point to note is the fairly late start of taking music lessons in this group of highly accomplished music students.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…However, the complete sample was relatively homogenous in musical competence, as the music students had passed entrance exams in high competition at prestigious music colleges. In accordance with the literature, vocal students started taking formal lessons later compared to instrumental students (Jørgensen, 2001, Sandgren, 2005). A point to note is the fairly late start of taking music lessons in this group of highly accomplished music students.…”
Section: Discussionsupporting
confidence: 55%
“…The difference might depend on the tradition of music tuition for vocalists. Vocalists in classical music often engage in choral singing in childhood and only later in the teens start taking singing lessons (Sandgren, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found increased levels of neuroticism, or emotionality, among professional vocalists (Marchant-Haycox & Wilson, 1992), vocal students (Kokotsaki & Davidson, 2003;Sandgren, 2005), elite chorus artists (Kenny, Davis & Oates, 2004), and musicians (Cooper & Wills, 1989;Dyce & O'Connor, 1994;Gillespie & Myors, 2000;Kemp, 1996;Wills, 1984). While assessing the role of neuroticism, it is important to consider the domain of work.…”
Section: Personality Dimensionsmentioning
confidence: 99%
“…Several studies are now beginning to emerge that explore the careers of professional musicians, such as the diversity of skills required by the contemporary musician (Mills, 2006; Bennett, 2007, 2008, 2009); the connection between music education and a musician's ability to earn a living (Coulson, 2010); factors contributing to stress in the lives of professional orchestral musicians (Brodsky, 2006; Dobson, 2011); and career development for professional opera singers (Sandgren, 2005). According to Bennett (2007), the majority of musicians spend more time teaching than performing and many supplement their income with low paid, unskilled or non-music related jobs.…”
Section: Work and A Musical Identitymentioning
confidence: 99%